Analisis Pengaruh Kualitas Layanan dan Promosi Terhadap Keputusan Pembelian Dengan Minat Beli Sebagai Variabel Mediasi: (Studi pada Konsumen Distro Kidheven Kabupaten Sukabumi) - Indriana, Hapivah; Antony, Antony; Amal, Muhammad Khairul (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2026)
This study analyzes the influence of service quality and promotion on purchase decisions with buying interest as a mediating variable in consumers of Distro Kidheven Sukabumi Regency. Local fashion retail competition requires distro managers to improve the service experience and optimize promotions to form buying interest that leads to purchase decisions. The study used a quantitative approach with purposive sampling techniques on 126 respondents who were consumers of Kidheven Distro. Data were collected through a Likert scale questionnaire of 1–5 and analyzed using AMOS-assisted Structural Equation Modeling (SEM) through the stages of measurement model test (CFA), structural model test, and direct influence testing and mediation. The results of this study showed that service quality had a significant positive effect on buying interest (C.R.=2.592; p=0.010), promotion had a significant positive effect on buying interest (C.R.=2.335; p=0.020), and service quality had a significant positive effect on purchase decisions (C.R.=3.633; p<0.001), in addition that promotion had a significant positive effect on purchase decisions (C.R.=2.253; p=0.024), and buying interest had a significant positive effect on purchasing decisions (C.R.=2.385; p=0.017). These findings confirm that buying interest strengthens the influence of service quality and promotion on purchasing decisions. The implications of the research are the need for standardization of services, reinforcement of physical evidence and employee interactions, and measurable and relevant promotions to market segmentation to maintain interest and increase purchase conversions.